الإعلام المتحفي ودوره في التعريف بالتراث الأثري - حدادي, وليدة (جامعة الوادي - University of Eloued, 2019)
Archaeological Museum play in contemporary societies effective roles, in order to preserve cultural and archaeological heritage,Through the availability and interpretation of this heritage by Using multiple media and communication mechanisms, because gaining public confidence is important to attract a large number of the local community, especially in light of the technological development witnessed by contemporary societies, where museums are cultural and educational institutions open to all, they have a responsibility of linking the future of man to the past, through Using means and mechanisms, the most important of which are the communication and media means used in the museum, to facilitate the access of visitors to the archaeological heritage collections exhibited in museums, such as movies, screens, recordings, scenes, lectures, websites, social networking sites, museum presentations on the Internet. Therefore, this research paper seeks to identify the importance of museum media in the definition of archaeological heritage.
مقال
Keywords: Archaeological Museum, Museum Media, Archaeological Heritage, Archaeological Awareness; المتحف الأثري,الإعلام المتحفي,التراث الأثرث,الو